Is that Financial Knowledge, Investment Experience, and Project Advertisement Have any Influence on Students’ Investment Intention in Sharia Crowdfunding? - Zakkya Jihan Nabilla; Atina Shofawati (Jurnal Ekonomi Syariah Teori dan Terapan, 2022)
ABSTRAK Crowdfunding Syariah merupakan salah satu bentuk fintech dengan mengumpulkan dana dari masyarakat untuk diberikan kepada pihak atau proyek yang membutuhkan bantuan dana dengan menerapkan prinsip syariah didalamnya. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh dari pengetahuan keuangan, pengalaman investasi mahasiswa dan iklan proyek terhadap minat investasi mahasiswa pada situs crowdfunding syariah di Indonesia. Pada penelitian ini digunakan metode kuantitatif dengan teknik analisis PLS-SEM. Dari hasil penelitian ditemukan bahwa pengetahuan keuangan dan iklan proyek berpengaruh signifikan terhadap minat investasi mahasiswa pada situs crowdfunding syariah, sedangkan pengalaman investasi mahasiswa memiliki pengaruh yang tidak signifikan pada minat investasi mahasiswa pada situs crowdfunding syariah di Indonesia. Kata Kunci: Pengetahuan Keuangan, Pengalaman Investasi, Iklan Proyek, Investasi Mahasiswa, Crowdfunding Syariah.   ABSTRACT Sharia crowdfunding is a form of fintech that collects funds from the public to be given to parties or projects that need financial assistance by applying sharia principles in it. This study aims to determine the effect of financial knowledge, investment experience, and project advertising on students’ investment intention in sharia crowdfunding sites in Indonesia. In this study, quantitative methods were used with PLS-SEM analysis techniques. It found that financial knowledge and project advertising had a significant effect on students’ investment intention in sharia crowdfunding sites, while students’ investment experience had an insignificant effect on the students’ investment intention in sharia crowdfunding sites in Indonesia. Keywords: Knowledge, Investment Experience, Project Advertisement, Students’ Investment, Sharia Crowdfunding.   DAFTAR PUSTAKA Alquraan, T., Alqisie, A., & Al Shorafa, A. (2016). Do behavioral finance factors influence stock investment decisions of individual investors? (Evidences from Saudi Stock Market). American International Journal of Contemporary Research, 6(3), 159–169. Awais, M., Fahad Laber, M., Rasheed, N., & Khursheed, A. (2016). Impact of financial literacy and investment experience on risk tolerance and investment decisions: Empirical evidence from Pakistan. International Journal of Economics and Financial Issues, 6(1), 73–79. Chou, S. R., Huang G. L., & Hsu H. L. (2010). Investor attitude and behavior towards inherent risk and potential in financial product. International Research Journal of Finance and Economics. Darmansyah, Fianto, B. A., Hendratmi, A., & Aziz, P. F. (2020). Factors determining behavioral intentions to use Islamic financial technology: Three competing models. Journal of Islamic Marketing, 12(4), 794–812. https://doi.org/10.1108/JIMA-12-2019-0252 Faidah, F. (2019). Pengaruh literasi keuangan dan faktor demografi terhadap minat investasi mahasiswa. JABE (Journal of Applied Business and Economic), 5(3), 251. https://doi.org/10.30998/jabe.v5i3.3484 Hardiwinoto. (2013). Teori dan praktik keputusan investasi sektor rill dan finansial. Semarang: Unimus Press. Hendratmi, A., Ryandono, M. N. H., & Sukmaningrum, P. S. (2020). Developing Islamic crowdfunding website platform for startup companies in Indonesia. Journal of Islamic Marketing, 11(5), 1041–1053. https://doi.org/10.1108/JIMA-02-2019-0022 Lacan, C., & Desmet, P. (2017). Does the crowdfunding platform matter? Risks of negative attitudes in two-sided markets. Journal of Consumer Marketing, 34(6), 472–479. https://doi.org/10.1108/JCM-03-2017-2126 Lubis, P. K. D. (2019). Influence of knowledge investment and investment motivation against the interest of investing in the stock market on economic education status of students of state university of Medan. Journal of Physics: Conference Series, 1387(1). https://doi.org/10.1088/1742-6596/1387/1/012064 Mishra, K. C., & Metilda, M. J. (2015). A study on the impact of investment experience, gender, and level of education on overconfidence and self-attribution bias. IIMB Management Review, 27(4), 228–239. https://doi.org/10.1016/j.iimb.2015.09.001 Nagy, A., & Obenberger, W. (1994). Influencing individual behavior investor. Financial Analysts Journal, 50(4), 63–68. https://doi.org/10.2469/faj.v50.n4.63 Nugroho, A. Y., & Rachmaniyah, F. (2019). Fenomena perkembangan crowdfunding di Indonesia. Ekonika: Jurnal Ekonomi Universitas Kadiri, 4(1), 34-46. https://doi.org/10.30737/ekonika.v4i1.254 Otoritas Jasa Keuangan. (2021). Statistik fintech lending periode Januari 2021. https://www.ojk.go.id/id/kanal/iknb/data-dan-statistik/fintech/Pages/Statistik-Fintech-Lending-Periode-Januari-2021.aspx Putra, S. M., & Susilowati, F. D. (2020). Pengaruh popularitas proyek dan kualitas informasi proyek pada kampanye crowdfunding. Jurnal Konsep Bisnis dan Manajemen, 7(November), 35–47. https://doi.org/10.31289/jkbm.v7i1.4225 Schwienbacher, A., & Larralde, B. (2012). Crowdfunding of small entrepreneurial ventures. SSRN Electronic Journal, 2010. https://doi.org/10.2139/ssrn.1699183 Suprihati., & Pradanawati, S. L. (2020). The influence of knowledge, investment motivation and investment understanding on student interest to invest in the capital market. International Journal of Economics, Business and Accounting Research (IJEBAR), 4(4), 1030–1038. Suyanti, E., & Hadi, N. U. (2019). Analisis motivasi dan pengetahuan investasi terhadap minat investasi mahasiswa di pasar modal. Edunomic Jurnal Pendidikan Ekonomi, 7(2), 108-116. https://doi.org/10.33603/ejpe.v7i2.2352 Taha, T., & Macias, I. (2014). Crowdfunding and Islamic finance: A good match? In Social Impact Finance (pp. 113–125). https://doi.org/10.1057/9781137372697_10 Tuyon, J., & Ahmad, Z. (2016). Behavioural finance perspectives on Malaysian stock market efficiency. Borsa Istanbul Review, 16(1), 43–61. https://doi.org/10.1016/j.bir.2016.01.001 Zheng, H., Li, D., Wu, J., & Xu, Y. (2014). The role of multidimensional social capital in crowdfunding: A comparative study in China and US. Information and Management, 51(4), 488–496. https://doi.org/10.1016/j.im.2014.03.003